Saving Preferences in Banking Institutions among West Java People Before Covid-19 - Hendajany, Nenny; Aprianti, Ine (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2025)
Abstract Saving represents residual income after consumption and contributes to economic growth through investment. This study aims to analyze the savings preferences of West Java residents, one of Indonesia’s most populous provinces. Data were derived from the 2018 SUSENAS, published in 2019, reflecting conditions before the Covid-19 pandemic. A savings ownership model was developed to capture preferences, with key determinants including expenditure, education, marital status, gender, age, place of residence (urban/rural), and district/city controls. The findings indicate that all variables significantly affect savings ownership. Expenditure, age, and the male dummy show negative coefficients, while education, marital status, and residence in urban areas display positive effects. Despite these influences, the proportion of savings holders in banking institutions remains relatively low in West Java. The study highlights the relevance of government policies, particularly during the Covid-19 pandemic, where channelling cash assistance through banks proved to be an appropriate and effective strategy. ABSTRAK Tabungan merupakan pendapatan sisa setelah konsumsi dan berkontribusi terhadap pertumbuhan ekonomi melalui investasi. Penelitian ini bertujuan untuk menganalisis preferensi menabung penduduk Jawa Barat, salah satu provinsi dengan jumlah penduduk terbesar di Indonesia. Data diperoleh dari SUSENAS tahun 2018 yang dipublikasikan pada tahun 2019 dan mencerminkan kondisi sebelum pandemi Covid-19. Model kepemilikan tabungan dikembangkan untuk menangkap preferensi menabung, dengan faktor penentu utama meliputi pengeluaran, pendidikan, status perkawinan, jenis kelamin, usia, tempat tinggal (perkotaan/perdesaan), serta variabel kontrol kabupaten/kota. Hasil penelitian menunjukkan bahwa seluruh variabel berpengaruh signifikan terhadap kepemilikan tabungan. Pengeluaran, usia, dan variabel dummy laki-laki menunjukkan koefisien negatif, sedangkan pendidikan, status perkawinan, dan tempat tinggal di wilayah perkotaan menunjukkan pengaruh positif. Meskipun demikian, proporsi pemilik tabungan di lembaga perbankan di Jawa Barat masih relatif rendah. Penelitian ini menyoroti relevansi kebijakan pemerintah, khususnya pada masa pandemi Covid-19, di mana penyaluran bantuan tunai melalui perbankan terbukti menjadi strategi yang tepat dan efektif.